18F-DCFPyL PET/CT in Newly Diagnosed Prostate Cancer: Diagnostic Value of Intraprostatic PSMA Uptake in Risk Classification of Prostate Cancer - Zhou, Shuoming; Liu, Tiantian; Zhu, Ziqiang; Zhang, Lin; Qian, Subo; Fu, Hongliang; Cao, Qifeng; Kang, Jian (Frontiers in Oncology, 2022)
Purpose 18F-DCFPyL prostate-specific membrane antigen (PSMA) PET/CT is commonly applied to locate lesions of prostate cancer (PCa), but its diagnostic function of quantitative parameters is ignored. Our study evaluates the parameters of intraprostatic PSMA uptake in patients newly diagnosed with PCa and explores their predictive value in risk classification, which is similar to D’Amico criteria. Materials and Methods We quantified the maximal standardized uptake value (SUVmax), mean SUV (SUVmean), total lesion (TL)-PSMA, prostate/muscle (P/M) ratio of the primary tumor, and PSMA-derived tumor volume (PSMA-TV) from 62 patients with histologically proven PCa. Patients newly diagnosed with PCa were allocated into risk groups (at low, intermediate, and high risk, respectively) in accordance with D’Amico criteria. Afterwards, the five parameters mentioned above among three different risk groups were compared, and their predictive values in the risk classification of PCa were explored. Results Significantly decreased levels of SUVmax, SUVmean, TL-PSMA, and P/M ratio were observed in the risk groups of low or intermediate or both, compared with the high-risk group. However, only the P/M ratio significantly elevated in patients with intermediate risk [mean ± SD (median): 46.58 ± 9.74 (45.27), P = 0.042] or high risk [98.95 ± 38.83 (97.52), P < 0.001], compared with low-risk patients [12.33 ± 5.93 (9.81)]. When P/M ratio was used to distinguish between low-risk and intermediate-risk patients, its c-statistics was 0.660. On the other hand, when distinguishing between intermediate-risk and high-risk groups, the c-statistics of P/M ratio was 0.667. Finally, when P/M ratio was used to distinguish between low-risk and high-risk patients, the c-statistics was 0.969. P/M ratio had a positive correlation with prostate-specific antigen in all enrolled PCa patients. Conclusion The quantitative parameters of 18F-DCFPyL PET/CT, including SUVmax, SUVmean, and P/M ratio, might assist in distinguishing low-risk or intermediate-risk groups from the high-risk group. Of these parameters, P/M ratio appears to be the better promising parameter for risk classification of prostate cancer than SUVmax.